2022
DOI: 10.3390/ijms23095108
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Skeletal Muscle Organoids from Human Pluripotent Stem Cells to Model Myogenesis and Muscle Regeneration

Abstract: In vitro organoids derived from human pluripotent stem cells (hPSCs) have been developed as essential tools to study the underlying mechanisms of human development and diseases owing to their structural and physiological similarity to corresponding organs. Despite recent advances, there are a few methodologies for three-dimensional (3D) skeletal muscle differentiation, which focus on the terminal differentiation into myofibers and investigate the potential of modeling neuromuscular disorders and muscular dystr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…In the culture, a WNT activator and BMP inhibitor are added for the first 3 to 5 days, allowing formation of the neuroectodermal lineage. When skeletal muscle is the only tissue required in the organoid, FGF2, HGF (hepatocyte growth factor), and IGF (insulin growth factor) are used to induce the dermomyotome [29][30][31]. If the formation of a neuronal muscular junction is desired, retinoid acid, Wnt1a, and Sonic hedgehog could be added to induce the neural tube following the neuromesoderm induction prior to the dermomyotome induction [32].…”
Section: Three-dimensional Myogenic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the culture, a WNT activator and BMP inhibitor are added for the first 3 to 5 days, allowing formation of the neuroectodermal lineage. When skeletal muscle is the only tissue required in the organoid, FGF2, HGF (hepatocyte growth factor), and IGF (insulin growth factor) are used to induce the dermomyotome [29][30][31]. If the formation of a neuronal muscular junction is desired, retinoid acid, Wnt1a, and Sonic hedgehog could be added to induce the neural tube following the neuromesoderm induction prior to the dermomyotome induction [32].…”
Section: Three-dimensional Myogenic Differentiationmentioning
confidence: 99%
“…Despite the exciting development of 3D cell culture, hiPSC-myogenic cell expansion has not been well adapted to the 3D culture system to date. There are few studies showing muscle cell lineage specification by forming 3D muscle organoids or spheroids that contain PAX7-expressing myogenic progenitor cells [29,33], but no purification was reported following the specification. For downstream hiPSC-derived myogenic cell expansion, one study showed that myoblasts can be cultured in a suspension as aggregates, but the majority of cells exit the cell cycle and do not proliferate [208].…”
Section: Manufacturing Challenges For Cell Expansionmentioning
confidence: 99%
“…Generally, the strategies to obtain 3D SkM models rely on self-organized 3D constructs or organoid-like cultures ( Li et al, 2011 ; Takahashi et al, 2013 ; Takahashi and Okano, 2015 ; Shin et al, 2022 ), and scaffold-based 3D models ( Jalal et al, 2021 ) even though the majority of protocols require the presence of scaffolds which can be of different composition and formulation. Currently, cells are embedded in Matrigel, collagen or fibrin hydrogels and the 3D constructs take place due to the presence of two attaching points able to provide proper physical cues as the tensile strength ( Ostrovidov et al, 2014 ; Gholobova et al, 2018 ; Laternser et al, 2018 ; Maffioletti et al, 2018 ; Afshar Bakooshli et al, 2019 ; Capel et al, 2019 ; Afshar et al, 2020 ; Fleming et al, 2020 ; Rajabian et al, 2021 ).…”
Section: 3d In Vitro Muscle Modelsmentioning
confidence: 99%
“…Rapid development of the isolation of adult stem cells from biopsies allowed the establishment of tissue-specific three-dimensional systems, or organoids. These achievements enable modelling of human organ development in a Petri dish including lung [ 11 ], skeletal muscle [ 12 ], bile duct [ 13 ], heart [ 14 ], neurone system [ 15 ] and hair-bearing skin [ 16 ].…”
Section: Introductionmentioning
confidence: 99%